Synthesis and characterization of metal sulfates loaded palm empty fruit bunch (PEFB) for biodiesel production - Rahila Ishfaq,; Nurun Najwa Ruslan,; Nursyafreena Attan,; Suzi Salwah Jikan,; Amira Saryati Ameruddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Biodiesel has been globally accepted as a green substitute for diesel fuel. However, the insecurity of food raised with the application of edible sources in biodiesel production has caused much debate. The feasible alternative technique is the use of inedible and low-grade sources such as palm fatty acid distillate (PFAD). In this work, the production of biodiesel (FAME) from PFAD using solid acid catalysts (SACs) derived from palm empty fruit bunch (PEFB) is investigated. The SACs were synthesized through impregnation of different metal sulfate precursors, i.e. ferrous sulfate heptahydrate (FeSO4.7H2O), copper sulfate pentahydrate (CuSO4.5H2O), and magnesium sulfate heptahydrate (MgSO4.7H2O) over PEFB. SEM-EDX observations found that impregnation and then calcination resulted in attachment of sulfur (S) and improved surface porosity. FT-IR analysis showed that there were distinct interactions between metal sulfates and PEFB. XRD characterization showed that the prepared catalysts have a crystalline structure. Besides, the catalytic activity of the SACs was closely associated with their acid densities measured by the titration method. Fe-PEFB catalyst showed the highest acid density (2.44 mmol/g) among the catalysts studied. To study the effect of process parameters on FFA conversion (%), optimization of methanol: PFAD molar ratio, catalyst dosage, reaction temperature, and reaction time was conducted. Maximum FFA conversion of 89.1% was obtained over Fe-PEFB while Cu-PEFB and Mg-PEFB achieved an FFA conversion of 63 and 56.5%, respectively, under the optimum reaction conditions. Thus, the present study offers a sustainable and environmentally benign method for biodiesel production.